Through our lens: an exploration of mental health while learning online as a training drama therapist during a global pandemic - Suntsha, Phindile Fortunate (My University, 2022)
This research is a qualitative exploration of the mental health of the Master of Arts in Drama Therapy (MADT) students at Drama for Life of which I am part of. The MADT class is based at the University of the Witwatersrand and the exploration includes both the students and lecturers while learning online during the COVID-19 global pandemic of 2020 in South Africa. This exploration is founded on the backdrop of social justice due to the limitations of accessing online learning during a global pandemic and how this is a contributory factor to mental wellness in both students and lecturers. 2020 has come and gone and the students have continued with their studies under the circumstances. Unfortunately some are still struggling with access learning and learning resources. This research is framed by Maslow’s theory of self-actualisation. This theory underpins that when one is healthy mentally which is an individual experience; one is able to function better and develop themselves. We develop ourselves and self-actualise through learning and taking care of ourselves. With all the challenges caused by the pandemic, online learning, and limited access, the MADT students and the lecturers have found ways to manage their mental health. The evidence from this qualitative exploration utilised Data Analysis Triangulation to arrive at the above conclusions. Through the conclusions made, aspects of the Omega Transpersonal approach to Drama Therapy are recommended as activities to include in one’s self-care routine to aid with mental wellness while learning online during and post the pandemic.
A dissertation submitted in partial fulfilment of requirements of degree of Arts in Drama Therapy by coursework and research report to the Faculty of Humanities, University of the Witwatersrand, 2021